Retrospective of the experimental morphological study of 1991 from the standpoint of evaluating the effectiveness of anterior dynamic correction of adult scoliosis - S.V. Kolesov; V.S. Pereverzev (Хирургия позвоночника)
The article reviews the dissertation work of M.M. Usmanov, “Changes in the Intervertebral Disc with Limited Damage to its Elements and Implantation of Various Materials: an Experimental Study”, defended in 1991. This study is of great interest to us in the light of the development and advancement of anterior dynamic correction of scoliosis in patients with completed and close to complete growth, where we believe the partial nucleotomy to be a key moment for ensuring optimal results. The dissertation describes an experimental morphological study on rabbits and convincingly proves that limited damage to the intervertebral disc elements can affect the strength properties of the spinal motion segment. A direct correlation between the morphological state of the intervertebral disc and the strength characteristics of the spine is shown. It was established that changes in the strength characteristics of spinal segments depend on the nature and amount of regenerating tissue in the intervertebral disc. This information can confirm and explain the effectiveness of the new approach to treating scoliosis.